Parkinson’s Disease Classification Using Inertial Signals from Smartwatches and Tree-Based Classifiers - Lobo, Pedro L. S.; Chagas, Ana Luísa de Bastos; Bucci, Giordana de Farias F. B.; Salvini, Rogerio L.; Soares, Fabrizzio A.; Felix, Juliana P. (Anais da Escola Regional de Informática de Goiás (ERI-GO); 2025: Anais da XIII Escola Regional de Informática de Goiás, 2025)
This study evaluates the use of statistical features extracted from inertial signals obtained from smartwatches to assist in distinguishing patients with Parkinson’s disease, differential diagnoses, and healthy controls. Using a public dataset comprising data from 469 individuals, tree-based classifiers were applied. The results indicate that simple motion information can support the diagnosis of Parkinson’s disease in a non-invasive and accessible manner.